1994
DOI: 10.1183/09031936.94.07101830
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early lung impairment with aerosol bolus dispersion

Abstract: The broadening of inhaled aerosol boluses (aerosol bolus dispersion) during respiration provides a noninvasive measure of convective gas mixing in the lungs. In this study, the sensitivity and specificity of this technique for the diagnosis of early lung impairment due to cigarette smoking was evaluated.Two hundred and sixteen randomly selected subjects (126 smokers and 90 nonsmokers) were investigated with aerosol dispersion in comparison to conventional lung function tests. The cumulative cigarette consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…5) were actually consistent with the ranges of values encountered in the literature using nonhygroscopic aerosols. Combing data from various previous reports (4,5,7,18) using nonhygroscopic aerosols in the 0.5-1 m size range, we found that H values for healthy subjects ranged 180-300 ml for VLD ϭ 200 ml and 400-600 ml for VLD ϭ 800 ml.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…5) were actually consistent with the ranges of values encountered in the literature using nonhygroscopic aerosols. Combing data from various previous reports (4,5,7,18) using nonhygroscopic aerosols in the 0.5-1 m size range, we found that H values for healthy subjects ranged 180-300 ml for VLD ϭ 200 ml and 400-600 ml for VLD ϭ 800 ml.…”
Section: Discussionmentioning
confidence: 95%
“…On the basis of previous observations by others (1,5,22) in which smokers were essentially characterized by a steeper increase of dispersion between shallow and deep VLD levels, we also computed for each subject the increase of the dispersion indexes H and between VLD ϭ 200 ml and VLD ϭ 800 ml [e.g., ⌬H ϭ H(800 ml) Ϫ H(200 ml)]. The resulting ⌬H and ⌬ are summarized in Table 2, in which smokers showed a significantly larger dispersion increment between 200 and 800 ml for ⌬H as well as for ⌬ (for cutoffs 5 and 15%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations